Biocontrol of Meloidogyne spp. in Solanum lycopersicum using a dual combination of Bacillus strains - Díaz-Manzano, Fernando Evaristo; Amora, Deisy X.; Martínez-Gómez, Ángela; Moelbak, Lars; Escobar, Carolina (Frontiers in Plant Science, 2023)
Root-knot nematodes (RKNs, Meloidogyne spp.) are obligate plant parasites that constitute a significant pest for agriculture worldwide. They penetrate the plant roots, reducing the uptake of water and nutrients, causing a significant impact on crop yield. One alternative on focus now for nematode management is biological control. Rhizobacteria within the Bacillus genus show multiple modes of action against plant-parasitic nematodes (PPNs) that can act alone or in combination. In this context, we evaluated a dual-strain bacteria combination (B. paralicheniformi FMCH001 and B. subtilis FMCH002) to reduce nematode infection in tomato plants. We evaluated mortality of larvae from Meloidogyne javanica in vitro, as well as eggs hatching after the treatment. Atraction, penetration, establishment, and reproduction assays in vitro or in pots in tomato plants infected with M. javanica and treated/ untreated with the dual-strain bacteria combination were also performed. Additionally, morphometric parameters comparing giant cells size from galls of treated and untreated plants by using confocal microscopy were also measured. The results showed that this combination of strains has nematicidal properties in the pre-infection phase by decreasing the egg-hatching, juvenile survival, and attractiveness to the roots. Furthermore, nematode establishment, gall formation, and, remarkably, giant cell development was severely impaired after the bacterial treatment, suggesting interference with morphogenetic mechanisms induced by the nematode during GCs development within the plant. Nematode reproduction in tomato plants was reduced independently of the application mode in soil, before or after bacterial treatment. The dual-strain combination was also effective against other PPNs (i.e. Pratylenchus spp.) and in different crops (soybean). Therefore, combining B. paralicheniformis FMCH001 and B. subtilis FMCH002 is an efficient agent for the biological control of Meloidogyne spp. by interfering with different stages of the nematode cycle as a result of multiple modes of action.